2015
DOI: 10.1111/nmo.12705
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐211 causes ganglion cell dysplasia in congenital intestinal atresia via down‐regulation of glial‐derived neurotrophic factor

Abstract: Our results indicate that overexpression of miR-211 suppresses the differentiation of BMSCs into intestinal ganglion cells by directly down-regulating the expression of GDNF. The findings elucidate the role of miRNA in congenital intestinal atresia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
2
6
0
1
Order By: Relevance
“…miRNA-211 is also reported to regulate glial-derived neurotrophic factor, a neurotrophic factor and key neurotrophin in the enteric nervous system (ENS). 34 In our study, we found that miR-211-5p was downregulated in the hippocampus of SHRs. Many studies have shown that Dyrk1a is a protein-coding gene that is closely related to the development and function of the brain.…”
Section: Discussionsupporting
confidence: 53%
“…miRNA-211 is also reported to regulate glial-derived neurotrophic factor, a neurotrophic factor and key neurotrophin in the enteric nervous system (ENS). 34 In our study, we found that miR-211-5p was downregulated in the hippocampus of SHRs. Many studies have shown that Dyrk1a is a protein-coding gene that is closely related to the development and function of the brain.…”
Section: Discussionsupporting
confidence: 53%
“…miR-211 is a neuron-related miRNA that can inhibit neuronal differentiation in Alzheimer's disease [24]. Xia et al found that GDNF was a target of miR-211, and GDNF was negatively regulated by miR-211 in retinal ganglion cells [25]. Moreover, bioinformatics software predicted the binding sites between MIAT and miR-211.…”
Section: Introductionmentioning
confidence: 99%
“…GDNF homeostasis is likely more complex and involves regulation at several non-transcriptomic levels ( d’Anglemont de Tassigny et al , 2015 ). For instance, Gdnf mRNA degradation is highly regulated by microRNAs ( Kumar et al , 2015 ; Xia et al , 2016 ; Zhang et al , 2019 ). However, a low basal level of expression is probably necessary to prevent over-activation of dopaminergic terminals and deleterious effects of GDNF.…”
Section: Discussionmentioning
confidence: 99%